Determinants of foreign direct investment in Malaysia/ Zaibedah Zaharum ... [et.al] - Zaharum, Zaibedah; Md Isa, Mohamad Azwan; A Latif, Ruziah; Md Isa, Muhammad Firdhaus (UiTM Cawangan Johor, 2024)
Foreign Direct Investment (FDI) occurs when one country invests in another. Multiple factors have contributed to fluctuations in FDI flows globally. This study investigates the impact of the macroeconomic variables on FDI in Malaysia. Data were collected for the period of 30 years from 1992-2021 and analysed using Multiple Linear Regression models. The study’s findings concluded that gross domestic product (GDP), inflation (INF), real interest rate (RIR), trade openness (TRA), unemployment rate (UNE) and exchange rate (EXC) are six major macroeconomic variables impacting FDI inflows. Results of the study reveal that gross domestic product (GDP), inflation (INF) and exchange rate (EXC) are positively related to foreign direct investment (FDI). This suggests that a robust domestic economic output, moderate inflation rates, and favourable exchange rates serve to attract foreign investment. However, the study reveals that the real interest rate (RIR), trade openness (TRA) and unemployment rate (UNE) are negatively related to foreign direct investment (FDI). Overall, this study contributes valuable insights into the intricate relationship between macroeconomic variables and FDI inflows in Malaysia, shedding light on how different economic factors collectively shape the investment landscape of the nation.